Viabilidade do “Crew Resource Management (CRM)” na indústria de transformação - Barreda de Campos, Ubirajara (2024)
Before the 1980s, research and investigations into aircraft accidents identified human errors as the main cause of aeronautical accidents. These failures primarily occurred in interpersonal communications, decision-making, and leadership. The solution provided by the industry, government, and aerospace agencies was to apply a set of training and practices based on psychological aspects and simulations, which were termed Crew Resource Management (CRM) and have since increasingly enhanced aircraft operations' safety. Other industries recognized the advantages of CRM and began applying it to their own operations, especially in high-risk industries. Despite numerous advancements and the use of high technology, the manufacturing industry faces challenges related to operational quality and safety, including those of employees and equipment. CRM could be a tool to mitigate negative consequences related to these challenges. This work aimed to summarize, through a Systematic Literature Review using the PRISMA method, how CRM is applied in various industries, particularly in manufacturing and non-civil aviation transportation. It also aimed to understand, using field research at an automotive manufacturer in south-eastern Brazil, whether a safety culture already exists and whether it could facilitate the implementation of CRM programs and training in the manufacturing industry. It also aimed to assess its congruences and discrepancies compared to the Systematic Literature Review. The results showed that, with well-crafted adaptations, CRM training can be applied across industries to enhance operational safety, productivity, and the quality of products and services.